The expression is 2xy
we will substitute x and y by the given values
x = -1/4 and y = 3
![2xy=2*((-1)/(4))*(3)](https://img.qammunity.org/2023/formulas/mathematics/college/5y0sgbpfldvi8d3ir2dvyick6t1v6u2qmv.png)
We put the values of y in the expression
Now we will calculate the value
![2xy=(2*-1*3)/(4)](https://img.qammunity.org/2023/formulas/mathematics/college/3y12fhngqnjikenypndmjatudnf2v33wdi.png)
We will multiply the numbers in the numerator
![2xy=(-6)/(4)](https://img.qammunity.org/2023/formulas/mathematics/college/e6lvl7003da6eeogcsk4g7n38l1hv0e8ft.png)
We will simplify the fraction by divide up and down by 2
![\begin{gathered} 2xy=(-(6)/(2))/((4)/(2))=(-3)/(2) \\ 2xy=-(3)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/4fm5035xuig85q4lbd7o1azls15u2p0j9q.png)